Circulating TCR γδ Cells in the Patients with Systemic Lupus Erythematosus - Ewa Robak; Jerzy Z. Błoński; Jacek Bartkowiak; Hanna Niewiadomska; Anna Sysa-Jędrzejowska; Tadeusz Robak (Hindawi Limited, 1999)
Systemic lupus erythematosus (SLE) is a disorder with a wide range of immunological abnormalities. The results of the studies undertaken in the last decade indicated that SLE pathogenesis was mainly connected with the breakdown of the activation control of B and T cells, generating humoral or cell-mediated responses against several self-antigens of affected cells. The last studies demonstrate that the role of γδ T lymphocytes in autoimmune diseases can be especially important. Flow cytometry techniques were used to investigate the number and percentage of TCR γδ T cells and their most frequent subtypes in peripheral blood of 32 patients with SLE and 16 healthy volunteers. We also correlated TCR γδ cells number with the level of T CD3+, T CD4+, T CD8+, and NK (CD16) cells (cytometric measurements) and SLE activity (on the basis of clinical investigations). Our studies were preliminary attempts to evaluate the role of that minor T cell subpopulation in SLE. Absolute numbers of cells expressing γδ TCR in most SLE blood specimens were significantly lower than in the control group (P<0.006). However, since the level of total T cell population was also decreased in the case of SLE, the mean values of the percentage γδ T cells of pan T lymphocytes were almost the same in both analysed populations (7.1% vs 6.3%, respectively). In contrast to Vδ2+ and Vγ9+ subtypes of pan γδ T cells, Vδ3+ T cells number was higher in SLE patients (20×10 cells/μl) than in healthy control group (2×2 cells/μl) (P=0.001). However, we found no differences between the numbers of pan γδ T lymphocytes and studied their subtypes in the patients with active and inactive disease. These cell subpopulations were doubled in the treated patients with immunosuppressive agents in comparison with untreated ones; however, data were not statistically significant. Our study indicated that Vδ3+ subtype of γδ T cells seems to be involved in SLE pathogenesis; however, we accept the idea that the autoimmunity does not develop from a single abnormality, but rather from a number of different events.